What do conservation biologists think about their job and working conditions?. (July 2017) - Ramos, Hazel Melanie; Mustafa, Michael; Primack, Richard; Campos-Arceiz, Ahimsa
Abstract: Most conservation biologists appear to enjoy their careers. However, conflicts between family and work interests can cause burnout, job dissatisfaction, and increased intentions to quit. We conducted questionnaire surveys among 92 conservation biologists attending a regional conference in Asia to investigate (1) what aspects of their jobs conservation biologists like or dislike, and (2) how conflicts between family interests (including activities focused on children, spouses and significant others, parents and other relatives, and activities related to these) and work interests affect job satisfaction and the intentions of conservation biologists to leave their jobs or the field of conservation biology. At work, conservation biologists most enjoyed fieldwork, research opportunities, interactions with people, and a sense of freedom; they most disliked raising and managing funds, working under stressful conditions with tight deadlines, and performing administrative responsibilities. Conservation biologists in our sample generally reported high levels of job satisfaction; however, many also reported that work frequently interfered with family activities, that they were disengaged with their work, and that they intended to search for another conservation biology position or leave the field entirely. Importantly, burnout (exhaustion and disengagement) was a key mediator between work-family conflicts and job satisfaction; that is, when work-family conflicts led to burnout—which happened frequently—people were more likely to be dissatisfied with their jobs and to consider quitting. Conservation biologists and their supervisors should consider taking steps to create healthier work environments—e.g., improve training, transparency about job duties, and family-friendly workplace policies. Engaged and emotionally balanced conservation biologists are likely to be more effective in their efforts to conserve Earth's biodiversity.